Navigating Mental Health Support in Tunisia’s Digital Age: Preferences, Challenges, and Paradoxes-An online survey - O. Chhaider; M. Lagha; A. Adouni; I. Ben Romdhane; W. Homri; R. Labbane (European Psychiatry, 2024)
Introduction The digital age has transformed mental health support in Tunisia. This study explores how individuals seek assistance for mental health concerns online, considering their comfort levels, preferences, and decision-making factors.